Research Culture in Higher Education: The Case of a Foreign Language Department in Mexico - Edith Hernández Méndez; María del Rosario Reyes Cruz (Universidad Nacional de Colombia, 2014)
In the case of Mexico, until recently, many universities focused mainly on teaching, but recent changes have led to new appointments in research, administration, and community service. There now seems to be, however, a view of the predominance of research in the academic environment. Therefore, the purpose of this paper was to examine and identify, through the lens of organizational theory and a current model of research culture in an academic setting, some characteristics of the research culture in the Department of Languages and Education at a public university in Southeast Mexico. Following the international tendencies and models in higher education, we see that the research culture observed in this university resembles more a market culture than other types of culture, although some traits of hierarchy culture provide cohesion in the organization.